PENERAPAN FUZZY INFERENCE SYSTEM METODE TSUKAMOTO DALAM EVALUASI PEMBELAJARAN SISWA DI YAYASAN AL LATHIIF KHOTIBUL AKHYAR - Raudhatul Syifa, Siti; Maulana Ardhiansyah (Teknik Informatika Universitas Pamulang, 2025)
This study aims to develop a learning evaluation system based on the Fuzzy Inference System (FIS) using the Tsukamoto method to improve the objectivity and efficiency of the assessment process at the Al Lathiif Khotibul Akhyar Foundation. Until now, the student assessment process at this tutoring institution has been conducted manually and subjectively. By using fuzzy logic, evaluation aspects such as discipline, concept understanding, and problem-solving can be assessed more measurably. The research results show that the developed system is capable of providing evaluations that are more accurate, consistent, and aligned with the actual conditions of the students. This system is implemented as a web-based application using PHP and MySQL, and tested using the black box method to ensure that all functions operate according to requirements. Keywords: Fuzzy Inference System, Tsukamoto Method, Learning Evaluation, Fuzzy Logic, Decision Support System